Incarceration, classification and control: Administrative detention in settler colonial Australia. (August 2021) - Nethery, Amy
Abstract: Administrative detention, a form of non-judicial incarceration, was a powerful tool of settler colonialism. Administrative detention enables governments to incarcerate whole categories of people, often indefinitely and under unregulated conditions, to manage perceived threats to national identity, integrity, or security. In Australia, various forms of administrative detention have been implemented almost continuously since British settlement. By treating different forms of administrative detention as variations of the same category of governmental power, this article depicts this form of incarceration as fundamental to the creation and character of settler colonial societies. The article develops a history of Australian administrative detention by identifying the striking similarities between three historical forms – Aboriginal reserves, quarantine stations, and enemy alien internment camps – and immigration detention in the present day. Administrative detention has been used to establish order and hierarchy in the settler colonial state by classifying populations into subgroups, and has contributed to the character of its culture: in particular, the precarious sense of belonging afforded to some categories of non-citizen, and the primacy of executive power in controlling these categories. The article offers an endogenous explanation for the entrenchment of immigration detention policy, despite its flaws and harms.